Understanding disability in healthcare: exploring the perceptions of parents of young people with autism spectrum disorder. Issue 19 (11th September 2022) - Wright Stein, Simone; Alexander, Rochelle; Mann, Jotvarinder; Schneider, Cory; Zhang, Sophie; Gibson, Barbara E.; Gabison, Sharon; Jachyra, Patrick; Mosleh, Donya
Abstract: Purpose: How autism spectrum disorder (ASD) is understood (i.e., as a medical problem or natural human variation) has profound implications for how healthcare services are designed and delivered. As the recipients of these services, children and families are highly invested in these debates, yet little research has sought to investigate their views. The purpose of this study was to explore parents' conceptualizations of ASD in relation to disability, and how they align with, or diverge from, conceptualizations they encounter within healthcare. Materials and methods: Nine semi-structured qualitative interviews were conducted with parents of children with ASD and thematically analyzed. Results: The accounts suggested that participants integrated multiple and sometimes contradictory conceptualizations of disability that reflected both "medical" and "social" models and sources of disablement. While the participants often advocated for acceptance and inclusion of their child, the label of "neurodiversity" was commonly rejected due to the concern for potential loss of funding for services. Conclusions: Study findings highlight the relationship between how parents conceptualize ASD and their experiences accessing supportive services within current delivery structures. Implications for ASD service providers emphasize accommodating parents' unique and evolving values and priorities for healthcare and their relation to current service systems. Implications for Rehabilitation: Parents conceptualizations of ASD both inform and are influenced by their experiences of accessing supportive services. This study highlights that parents' perspectives are fluid, context-dependent, and do not exclusively represent a single model or perspective of disability. To meet family needs, service providers including healthcare professionals must recognize parents' unique understandings of their child's ASD and appreciate how healthcare shapes these perceptions.